Instructors' Reflection on Positive Behavior Support in RULES Foundation's EFL Classroom - Muhammad Kurniawan Rachman; Hanna Hanna; Aris Badara (Institut Agama Islam Negeri (IAIN) Kendari, 2019)
Students’ challenging behavior becomes one of the big issues in education nowadays and language education is not an exception. Therefore, preparing teachers insight towards the issue is essential as the first step to prevent the issue grows in the future. Positive Behavior Support appears as one of the solutions to this issue in developing countries such as Australia and Singapore in 2011. Supporting this system, the researcher perceived that it is vital to apply this system in the EFL classroom in Indonesia. This paper aims to investigate the instructors’ Reflection using Positive Behavior Support (PBS) in EFL classroom. The research used qualitative study and involved 3 instructors in an institution which applies EFL teaching as the program, also conducted an interview after the workshop and teaching to find more detail information in the data obtained. The finding of the study indicated that PBS in form of workshop positively supported the instructors’ teaching application when they were experiencing real teaching class situation using the support system. The instructors also perceived that having PBS workshop added their knowledge to support students’ behavior in their classroom and in the future positively. Unfortunately, two instructors denoted that they could not apply all the PBS parts in their teaching application since most of the students are adult learners. However, the instructors reported that through the workshop and teaching period they perceived a change in students’ positive behavior and PBS changes their paradigm toward teaching management system.